TESTING POTATO COLLECTION SAMPLES FOR THE PRESENCE OF GENES FOR RESISTANCE TO PHYTOPATHOGENS BY MEANS OF DNA MARKERS - A. B. Saynakova; M. S. Romanova; S. N. Krasnikov; O. V. Litvinchuk; Ya. I. Alekseev; A. V. Nikulin; E. V. Terentjeva (Вавиловский журнал генетики и селекции)
The development of phytopathogen-resistant varieties is the most reliable and economic way to reduce potato yield losses. Breeding of such varieties is possible by using genetic sources of resistance. The use of DNA markers for identification of valuable genotypes, including forms with several resistance genes, makes it possible to significantly improve breeding efficiency. The development of a multiplex PCR technique and using it to simultaneously test varieties and breeding lines for several genes that control the resistance to viruses and nematodes is a new approach to using DNA markers. This study is aimed at screening samples from the collection of the Narym Department of  Breeding and Seed Production of the Siberian Research Institute of Agriculture and Peat (the Branch of the Siberian Federal Agrobiotechnology Research Center, the Russian Academy of Sciences) using the multiplex PCR technique, for genes for resistance to Globodera rostochiensis and Globodera pallidas, potato wart disease, viruses X and Y. 40 samples were tested by means of genetic markers to identify genes for resistance to potato wart disease (Sen1), virus X (Rx), virus Y (Ryadg, Rychc, Rysto), Globodera rostochiensis (H1, Gro1-4) and Globodera pallida (Gpa2), in the genome. The sample included two varieties, three populations produced by self-pollination of the Ideal variety, and 35 individually selected potato hybrids. As a result, we identified marker NL25 (Sen1) in 19 samples; marker PVX (Rx) in 13 samples; marker RYSC3312 (Ryadg) in 10 samples; marker YES3-3A341 (Rysto) in 5 samples; markers TG 689141, 57R450, N195337 (H1) in 12 samples; marker Gro1-4-1602 (Gro1-4) in 6 samples; marker Gpa2-2452 (Gpa2) in 13 samples. In terms of economically valuable traits, sample С-31-15 is noted for high yield and quality indicators. It carries genes for resistance to potato virus X (Rx), Y (Rysto), Globodera rostochiensis (H1, Gro1-4), and Globodera pallida (Gpa2).